(untitled) - Champernowne, David Gawen (Cambridge UK, 1998)
Economic inequality has become a focus of prime interest for economic analysts and policy makers. This book provides an integrated approach to the topics of inequality and the personal income distribution. It covers the practical and theoretical bases for inequality analysis and income distribution as well as providing applications to real world problems. Special attention is given to an assessment of the merits and weaknesses of standard economic models and to illustrating the implications of distributional mechanisms using real data and illustrative examples.
Keywords: Equality,Income distribution,Bình đẳng,Phân phối thu nhập,Income,Thu nhập